HISTOLOGICAL AND HISTOCHEMICAL STUDIES ON THE MALE REPRODUCTIVE SYSTEM OF TALORCHESTIA MARTENSII (WEBER) (CRUSTACEA : AMPHIPODA) - LALITHA, M.; SHYAMASUNDAR, K.; RAO, KHANUMANTHA (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1992)
The morphological, histological and histochemical details of the male reproductive system have been described in the amphipod, Talorchestia martensii. Mature tests contain spermatogonia, spermatocytes, spermatids and spermatozoa in the lumen of the follicle. A battery of histochemical reactions revealed the chemical nature of the secretions from the testes and was deferens and various chemical changes taking place during the development of the male gametes.